(untitled) (Revista do Centro de Estudos Portugueses, 1999)
Este ensaio propõe-se a analisar o romance O ano da morte de Ricardo Reis, de José Saramago, sob o ponto de vista de sua configuração intertextual, discutindo não só o estatuto paródico que o romance parece assumir em relação aos discursos que glosa, mas também a forma pela qual este estatuto acaba por configurar uma imagem do Portugal salazarista, ativando uma discussão em torno das relações que se podem estabelecer, no texto literário, entre a História e a Ficção. The intertextual weaving of O ano da morte de Ricardo Reis is founded mainly on the appropriation of two discourses: one, literary – Fernando Pessoa’s and his heteronym’s discourses (which gives the novel his title) –, and another, referencial - the discourse of the newspapers read by Reis, which propagates Salazarist ideology in 1936. The description of the modes of intertextual weaving and the debate on the manner these discourses interact reveal the ironical status of the narrative, on which the questioning of history by fiction – carried out by the novel – is based.